DEFINITION OF THE SUBSOIL RESOURCES USE STAGE WITH GEOLOGICAL-ECONOMICAL AND ECOLOGICAL INDICES BY THE EXAMPLE OF WESTERN DONBAS REGION - Zakchariy, N.; Kurylo, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Problems of depletion process are examined by the example of Western Donbas region. Changes of ecological-geological indices depending on minerals using activity are analyzed. It was defined that Western Donbas region had characteristic of the stage of intense using.